A study on the quality-embedded efficiency measurement in DEA. Issue 2 (3rd April 2018) - Park, Jaehun; Sung, Si-Il; Kim, Yong-Jeong; Lee, Byungkwon; Bae, Hyerim
ABSTRACT: Data envelopment analysis (DEA) has been widely used to measure organizational efficiencies and quality among decision-making units (DMUs). General DEA for efficiency measurement, however, does not consider the positive relation between quality and output factors. In this paper, we propose a new DEA-based efficiency evaluation model that applies the positive relation between quality improvement and profits provision, and we suggest benchmarking information that is separated for quality and quantity improvement, respectively. The proposed model evaluates efficiency using new outputs obtained by multiplying the relative quality score by each DEA-output profit factor. In this way, it provides for more accurate discrimination in performance evaluation as well as a practical benchmark target for the improvement of inefficient DMUs. To illustrate the effectiveness and demonstrate the advantages of the proposed method, we conducted efficiency evaluations and benchmarking for 13 Korean national university hospitals.